Exposure to High Aerial Ammonia Causes Hindgut Dysbiotic Microbiota and Alterations of Microbiota-Derived Metabolites in Growing Pigs - Tang, Shanlong; Zhong, Ruqing; Yin, Chang; Su, Dan; Xie, Jingjing; Chen, Liang; Liu, Lei; Zhang, Hongfu (Frontiers in Nutrition, 2021)
The intestinal microbiome has been proven to affect host systematic metabolism and immune homeostasis. the current study aimed to investigate how aerial ammonia exposure influences the hindgut microbiota and its metabolites in the pig model. Twelve growing pigs were treated with or without aerial ammonia (35 mg/m3) for 25 days, and then the microbial diversity and microbiota-derived metabolites were measured. The results demonstrated that a decreased trend of leptin (p = 0.0898) and reduced high-density lipoprotein cholesterol (HDL-C, p = 0.0006) were observed in serum after ammonia exposure. Besides, an increased trend of hyocholic acid (HCA), lithocholic acid (LCA), hyodeoxycholic acid (HDCA) (p < 0.1), a decreased trend of tauro-deoxycholic acid (TDCA, p < 0.1) and reduced tauro-HDCA (THDCA, p < 0.05) were found in the serum bile acid (BA) profiles after ammonia exposure. Ammonia exposure notably raised microbial alpha-diversity with higher Sobs, Shannon or ACE index in cecum or colon and Chao index in cecum (p < 0.05), and exhibited a distinct microbial cluster clearly in hindgut indicated by principal co-ordinates analysis (p < 0.01), indicating that ammonia exposure induced alterations of microbial community structure and composition in the hindgut. Further analysis displayed that ammonia exposure increased potential harmful bacteria Negativibacillus, Alloprevotella or Lachnospira, and decreased beneficial bacteria Akkermansia or Clostridium_sensu_stricto_1 in the hindgut (FDR < 0.05). Analysis of microbiota-derived metabolites in hindgut showed that ammonia exposure increased acetate and decreased isobutyrate or isovalerate in cecum or colon, respectively (p < 0.05). Unlike the alteration of serum BA profiles, cecal BA data showed that high ammonia exposure had a decreased trend of cholic acid (CA), HCA, LCA (p < 0.1), and decreased deoxycholic acid (DCA), HDCA (p < 0.05), but increased glycol-chenodeoxycholic acid (GCDCA, p < 0.05). Mantel test and correlation analysis revealed associations between microbiota-derived metabolites and ammonia exposure-responsive cecal bacteria. Collectively, our findings illustrated that high ammonia exposure induced the dysbiotic microbiota in the hindgut, thereby affecting the production of microbiota-derived short-chain fatty acids and BAs, which play a pivotal role in the modulation of host systematic metabolism.